Adaptive medical courseware system for medical student - Norhasnida, Hasanuddin (2013)
Courseware system are the independent learning at many years now, have many learning system using online and technology system. This paper discuss the medical courseware that an effectiveness of this courseware with user knowledge level. This tutoring system will illustrates the many task until the student really understand about their syllabus (Dengue Fever). The main objective of this project is to develop tutoring courseware system for medical student at dengue fever syllabus. The implementation of this system will help to reduce the problem that faces of many medical students having their learning using the traditional way such as book. This system is developed using waterfall model approach ADDIE model. This project is expected to become a suitable teaching material that captures students' interest in the studies by using interactive multimedia. This courseware is developed by using the Adobe Author ware 7.